Quantitative determination of the optimal temporoparietal fascia flap necessary to repair skull‐base defects. Issue 11 (7th July 2020) - Siu, Alan; Rangarajan, Sanjeet V.; Rabinowitz, Mindy R.; Luginbuhl, Adam; Rimmer, Ryan A.; Chitguppi, Chandala; Farrell, Christopher; Nyquist, Gurston G.; Rosen, Marc R.; Evans, James J.
Abstract : Background: The ability to reconstruct large cranial base defects has greatly improved with the development of pedicled vascularized flaps. The temporoparietal fascia flap (TPFF) is a viable alternative to the Hadad‐Bassagasteguy nasoseptal flap for large ventral skull‐base defects. This study aims to characterize the size of the TPFF necessary for optimal ventral skull‐base reconstruction. Methods: Eleven formaldehyde‐fixed cadaveric heads were used to harvest TPFF of varying heights on each side (total = 22). TPFF was passed through the pterygomaxillary fissure (PMF) to the ventral skull base to assess its coverage. For a subgroup of 12 sides, the TPFF was trimmed to determine the minimum height necessary for coverage. Results: The TPFF height was (mean ± standard deviation [SD]) 14.72 ± 1.02 cm (range, 12.5 to 16.5 cm) and width was 8.43 ± 1.05 cm (range, 6 to 10.5 cm). The distance from the TPFF pedicle through the PMF was 5.8 ± 0.5 cm (range, 5 to 6.5 cm). All TPFF flaps provided complete ipsilateral coverage of clival defects, and all but 1 covered the entire clivus. All TPFF flaps, when rotated anteriorly, provided coverage up to the cribriform plate. The minimum TPFF height necessary for complete coverage of cribriform defects and ventral defects up to the planum sphenoidale was 12 cm. TPFF height for specimens with and without complete ventral skull‐base coverage was significantly different ( p < 0.0001). Conclusion: The TPFF is a versatile alternative to the nasoseptal flap and a height of at least 12 cm can provide enough coverage for all ventral skull base defects.